2022
DOI: 10.1111/cdoe.12832
|View full text |Cite
|
Sign up to set email alerts
|

Attrition of dental therapists in South Africa—A 42‐year review

Abstract: Professionals leave their positions for varied reasons. Attrition is defined as a gradual reduction of the workforce, which may be due to either voluntary or involuntary factors. 1 Involuntary factors are factors that either the employer or employee has no control over, such as retirement, ill health or death, while voluntary factors are those that lead to resignation but can be prevented or addressed by the employer. 1 Voluntary factors that influence attrition may include people seeking improved remuneration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…With only two universities training dental therapists in South Africa [ 4 ], the finding that many dental therapists did not intend to enroll for the degree is concerning, particularly for other universities that may consider offering dental therapy training. Training institutions need to consider how to make this profession more attractive to prospective students to address the issue of underproduction, which was flagged in the recent 42-year review of the dental therapy profession in South Africa [ 14 ]. There is also a need to expand training to dental schools in other provinces to both increase the annual production and geographic coverage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With only two universities training dental therapists in South Africa [ 4 ], the finding that many dental therapists did not intend to enroll for the degree is concerning, particularly for other universities that may consider offering dental therapy training. Training institutions need to consider how to make this profession more attractive to prospective students to address the issue of underproduction, which was flagged in the recent 42-year review of the dental therapy profession in South Africa [ 14 ]. There is also a need to expand training to dental schools in other provinces to both increase the annual production and geographic coverage.…”
Section: Discussionmentioning
confidence: 99%
“…The Western Cape is among the provinces with the highest prevalence of dental caries [ 6 ]. However, there was only one dental therapist employed in the public sector in the Western Cape out of the 714 who were registered in SA in 2019 [ 14 ]. Only two out of six dental schools in South Africa train dental therapists [ 14 ], which raises concerns about production of this cadre of mid-level oral health professionals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review of HCPSA records also reported an unequal distribution of dental therapists across South African provinces, with most located in KZN (44%) and Gauteng (27%). 11 To ensure equitable distribution of dental therapists throughout the country, training offerings should either be expanded to other provinces or existing programmes should consider more targeted recruitment of future students to be more reflective of underserved provinces.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent South African nationwide study of dental therapist attrition reported 40% attrition over a 42-year period and attrition of 9% over the 10-year period of 2009-2019. 11 Voluntary workforce attrition is a major public health problem globally, which may lead to staff shortages. Some of the downstream effects of voluntary attrition are increased workload, unavailability of healthcare workers and limited access to healthcare, leading to a higher burden of untreated diseases.…”
Section: Introductionmentioning
confidence: 99%